Prawne aspekty produkcji i wykorzystywania biogazu rolniczego w Polsce - Błażejewska, Kamila (Wydawnictwo Naukowe UAM, 2010)
The aim of this discussion is to determine whether and to what degree the legal regulations concerning the production and utilization of agricultural biogas affect the development of this branch of renewable sources of energy. In conclusion the author states among other things that regulations on agricultural biogas production and utilisation, binding to date, are insufficient to strengthen this branch of economy, there are no regulations referring directly to the construction conditions and principles of operation for agricultural biogas plants. Inconclusiveness of law does not promote future investments and reduces profitability of already existing installations. The situation is going to improve after the Act on the amendment to the Act on Energy Law, enacted on 8 January 2010, enters into force, realising the main proposals formulated in the strategic document “Innovative Economy – Energy agriculture”. However, it seems unlikely to have a biogas plant in every commune by the year 2020, as it is planned. This ambitious plan requires legislative measures being an effect of a comprehensive approach to regulations concerning agriculture, the environment and the energy sector.

L’autrice si propone l’obiettivo di rispondere alla domanda se, e in quale misura, la regolazione giuridica della produzione e dell’utilizzo del biogas agricolo incida sullo sviluppo di tale settore delle fonti energetiche rinnovabili. Nelle conclusioni si constata che le previsioni finora esistenti sono insufficienti per rinforzare l’economia del settore in questione. Manca una diretta disciplina delle condizioni di costruzione e dei principi del funzionamento degli impianti di biogas agricolo. Inoltre, l’equivocità della legge non favorisce gli investimenti futuri e abbassa la rendita degli impianti già esistenti. La situazione migliorerà dopo l’entrata in vigore della legge approvata l’8 gennaio 2010 di modifica della legge “Diritto energetico”, volta a realizzare i principali auspici formulati nel documento strategico „L’economia Innovativa – L’agricoltura energetica”. È tuttavia incerto se si riuscirà di costruire, come si intende, un impianto di biogas in ogni comune entro il 2020, poiché questo piano ambizioso richiede soluzioni legislative che siano il risultato di un approccio integrato delle normative agricole, ambientali ed energetiche.